Impact of cooperatives on smallholders' commercialization behavior: Evidence from Ethiopia - Bernard, Tanguy; Taffesse, Alemayehu Seyoum; Gabre-Madhin, Eleni Zaude (Wiley, 2008)
This article examines the impact of marketing cooperatives on smallholder commercialization of cereals using detailed household data in rural Ethiopia. We use the strong government role in promoting the establishment of cooperatives to justify the use of propensity score matching to compare households that are cooperative members to similar households in comparable areas without cooperatives. The analysis reveals that although cooperatives obtain higher prices for their members, they are not associated with a significant increase in the overall share of cereal production sold commercially by their members. However, these average results hide considerable heterogeneity across households. In particular, we find that smaller farmers tend to reduce their marketed output as a result of higher prices, whereas the opposite is true for larger farmers.